Phosphorylating and dephosphorylating protein complexes in bacterial chemotaxis. - Wang, H (1997)
During optimal motility conditions, a 1:1 stoichiometry of CheA(L) (654 amino acids) to CheA(S) (557 amino acids) was determined. It was also found that CheZ binding to CheA(S) was inhibited by CheA(L)-CheA(S)-CheW interaction. This suggests that CheA(S) has different functions in the phosphorylating complex (CheA(L)-CheA(S)-CheW) and in the dephosphorylating complex (CheA(S)-CheZ).